2014
DOI: 10.1155/2014/689157
|View full text |Cite
|
Sign up to set email alerts
|

A Paradoxical Triad: Scapulothoracic Dissociation with Clavicle and Humeral Shaft Fractures

Abstract: Scapulothoracic dissociation involves varying degree of discontinuity of the upper extremity from its truncal attachment. An eighteen-year-old male presented to the accident and emergency department following a motor vehicle accident where he was hit by a four wheeler while riding a two wheeler. He had tenderness and deformity over the left clavicle and the left humerus. He was unable to perform active wrist and finger dorsiflexion. A CT subsequently revealed a grade 2 splenic laceration. The splenic laceratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Moreover, a simultaneous extremity fracture is not rare, with a coincidence of humerus, radius, ulna, and hand fractures of 41% in patients with SD [ 8 , 15 ]. Similar published studies have reported cases of concomitant humeral and forearm fractures [ 3 , 9 , 16 ] that were surgically treated in the same stage with the SD, and once the critical phase was under control.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, a simultaneous extremity fracture is not rare, with a coincidence of humerus, radius, ulna, and hand fractures of 41% in patients with SD [ 8 , 15 ]. Similar published studies have reported cases of concomitant humeral and forearm fractures [ 3 , 9 , 16 ] that were surgically treated in the same stage with the SD, and once the critical phase was under control.…”
Section: Discussionsupporting
confidence: 69%
“…Concerning the treatment of bony injuries, there are no widely accepted treatment guidelines in the literature. Many authors prefer to proceed firstly to ORIF of the clavicle fracture, this way, protecting the underlying vascular and neurological repair [ 3 , 9 , 16 ]. The same was performed in both of our cases.…”
Section: Discussionmentioning
confidence: 99%